Smart and cognitive solutions for Operator 4.0: Laboratory H-CPPS case studies. (January 2020) - Zolotová, Iveta; Papcun, Peter; Kajáti, Erik; Miškuf, Martin; Mocnej, Jozef
Highlights: Physical and cognitive interaction in Industry 4.0. Human Cyber-Physical Production Systems in practice with our case studies and solutions. HMI and M2P interaction based on operator position. The concept of cognitive healthcare. Solutions for Operator 4.0 have better interactions, react time, cognitive access and HMI content. Abstract: This paper refers to the physical, sensing, and cognitive interaction in the Industry 4.0 concept and presents Human Cyber-Physical Production Systems in a laboratory environment. The Industry 4.0 defines new demands for productivity and effectiveness in production, which inevitably influences operators as well. A traditional operator is being transformed to the Operator 4.0. In this paper, we describe evolving roles of the operators in the factories. There are many ways to enhance the operator's physical, sensing, and cognitive capabilities. Given case studies are based on the defined Operator 4.0 typology. Types can be used individually or in combination to put humans into the center of technological revolution. We also describe our laboratory case studies developed during the previous research. We have focused on legacy systems, healthcare monitoring platform, the concept of predictive maintenance, and machine to people interaction system based on operator position. These case studies illustrate the possible applications of smart and cognitive solutions for the Operator 4.0. The obtained results are then evaluated by a set of criteria to compare legacy systems with our laboratory case studies based on the Operator 4.0 concept.